Ventilator Withdrawal Dilemma" in contemporary Islamic Law (Contemporary Fiqh), the Ethical Implications of Joint Decision-Making and the Maqasid al-Shariah Perspective - Adrianto; Haslinda (QISTHOSIA : Jurnal Syariah dan Hukum, 2025)
Fatwas from various scholars and Islamic jurisprudence councils generally permit the withdrawal of ventilator support or the cessation of life-sustaining treatment if the patient is in a terminal condition and medical treatment is deemed futile, allowing death to occur naturally. This differs from active euthanasia (lethal injection) which is strictly forbidden (haram) in Islam.  The relevant methodology is a qualitative, multidisciplinary (interdisciplinary) research approach focusing on library research and content analysis. This approach is crucial for bridging the gap between clinical biomedical ethics and Islamic legal traditions, The study results indicate that first, In contemporary Fiqh (Islamic jurisprudence), the withdrawal of ventilator support for patients with a minimal prognosis is permissible, with emphasis on the principle of avoiding futility (la darar wa la dirar - no harm inflicted or reciprocated) and the priority of preserving life (hifz al-nafs) in accordance with the perspective of Maqasid al-Shariah (the objectives of Shariah). This decision involves joint decision-making between the medical team, the patient (or their guardian), and religious scholars (ulama). second, The practical implications of shared decision-making (SDM) among the patient, family, and physician in the dilemma of ventilator withdrawal are significant, These implications include: Ethical and Legal Decision-Making, Improved Patient-Centered Care: Emotional Support for Families: and Strengthened Doctor-Patient/Family Relationships: third, The main normative contribution of maqasid al-shariah (objectives of Shariah) in navigating the dilemma of ventilator withdrawal lies in balancing the fundamental objective of preserving life (hifz al-nafs) with the principle of avoiding harm and hardship (maslahah and darurat avoidance).